2013
DOI: 10.2298/jsc121203037s
|View full text |Cite
|
Sign up to set email alerts
|

Selective liquid phase oxidation of glycerol to glyceric acid over novel supported Pt catalysts

Abstract: Several supported platinum catalysts were prepared by extractive-pyrolytic method for the selective glyceric acid production from glycerol. Al2O3, Y2O3, Lu2O3, ZrO2-Y2O3 TiO2, SG, Fe2O3, γ-AlO(OH) and C were used as catalyst supports, glycerol oxidation was carried out in the alkaline solutions and oxygen was used as oxidant. The optimal catalyst preparation parameters and glycerol oxidation conditions to obtain glyceric acid were determined. The best result (selectivity to glyceric acid 57% with glycero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…However, when xylose and glycolic acid or tartaric acid mixture was used as substrate, there are unconverted glycolic or tartaric acid in the solution, suggesting decarboxylation of tartaric acid or glycolic acid could be slow because of surface coverage by xylaric acid or xylonic acid. Prior studies on decarboxylation of glycerol over platinum and cobalt catalysts, or complete conversion oxalic acid to carbon dioxide on a platinum catalyst agree with our observation. On the basis of above discussion, we propose a plausible reaction pathway in Scheme .…”
Section: Resultssupporting
confidence: 91%
“…However, when xylose and glycolic acid or tartaric acid mixture was used as substrate, there are unconverted glycolic or tartaric acid in the solution, suggesting decarboxylation of tartaric acid or glycolic acid could be slow because of surface coverage by xylaric acid or xylonic acid. Prior studies on decarboxylation of glycerol over platinum and cobalt catalysts, or complete conversion oxalic acid to carbon dioxide on a platinum catalyst agree with our observation. On the basis of above discussion, we propose a plausible reaction pathway in Scheme .…”
Section: Resultssupporting
confidence: 91%
“…[10,28] The catalytic activities were compared for different catalysts based on TOF calculated for < 20% glycerol conversion and using Pt metal dispersion (% of surface to bulk Pt content, see Table S1 for details). As shown in Figure 3 (d 11,295.1±1841.9 h -1 , respectively), manifesting remarkable synergistic effects. Moreover, the tartronic acid yield (after 24 h) on bimetallic PtFe(1) and PtFe(1)-a catalysts is about 37−42%, much greater than values observed with monometallic Pt and Fe catalysts (3−14%).…”
Section: Catalyst Synthesis Characterization and Performance Evaluationmentioning
confidence: 74%
“…Pt, Pd) often prevents further (oxidation) reactions. [11,12,28] The high tendency for decarboxylation or oxidative decarbonylation, due to strong interactions noted in the literature, is known to lead to significant side reactions such as CO formation and resultant catalyst poisoning at low temperature. [29] Clearly, the strong interaction demands higher activation energy for transformation of −C=O groups (in glyceraldehyde or glyceric acid molecules) on monometallic Pt catalyst surface (orange route in Figure 11).…”
Section: Pt and Fe Element Dispersion Within Bimetallic Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…We also compared the glucose oxidation results of this work with reported glycerol (a C 3 sugar polyol) oxidation results over Pt-based catalysts. In the cited studies on glycerol oxidation, poor liquid-phase carbon balance (67–85%) was reported when glycerol conversion was high (>30%, 50–90 °C). , This is because once the CO bond (i.e., carbonyl species) was formed from glycerol, decarbonylation catalyzed by noble metals led to a side reaction generating CO, which either deactivated the catalysts or formed CO 2 (in the form of carbonate salt) in the reaction medium. These products could not be quantitatively assessed by HPLC.…”
Section: Resultsmentioning
confidence: 99%